The Role of Dynamical Transition in Protein Function: Coupling of Protein Collective Vibrations and Water Dynamics - Xu, Mengyang; Niessen, Katherine; Deng, Yanting; Michki, Nigel; Snell, Edward; Markelz, Andrea (30th Anniversary Symposium of The Protein Society, 2016)
Computational simulations have revealed protein collective vibrations prompt structural rearrangements to accomplish biological function. However, the biological importance of collective vibrations has not been experimentally demonstrated. The attempts have been hampered by the inability to distinguish localized water or side-chain relaxational motions from protein long-range vibrations using conventional techniques. The dynamical transition (DT), extensively observed using X-ray, neutron scattering, NMR and terahertz techniques [1,2], describes a rapid increase in the temperature-dependent dynamics of critically hydrated proteins above ∼220 K, and has been attributed to thermally activated solvent motions. While some proteins lose function below the specific temperature, others do not. We suggest the difference arises from the nature of the required motions for function. Specifically, functional motions enabled by long-range vibrations will be vulnerable to DT, which require surrounding solvent to be sufficiently mobile. We explored the coupling of protein vibrations to solvent dynamics by applying a recently developed technique, anisotropy terahertz microscopy [3], to directly measure the collective vibrations for lysozyme and investigate the temperature dependence in 150-300 K range. We find long-range intramolecular vibrations occur at 220K and rapidly increase in strength with increasing temperature, consistent with enhanced access above the DT. The results suggest collective vibrations are slaved to DT, and those proteins with function reliant on these motions will cease function below DT. 1. Doster,W., et al. Phys.Rev.Lett., 2010.104(9):098101. 2. Niessen,K., et al. Biophys.Rev., 2015.7,201. 3. Acbas,G., et al. Nat.Commun., 2014.5,3076.